Factors Influencing Parents’ Decisions on Choosing an Islamic Primary School in Bandung Indonesia - Dian Hidayati; Andi Arif Rifa’i (Randwick International of Social Science Journal, 2020)
The era of disruption has brought about the impact of fundamental changes in the digital-based information presentation globally. Easy access to information and communication through social networks makes children no longer care about the surrounding environment and tends to be "uncivilized". The condition makes parents try to instill a filter through the selection of schools with a religious character curriculum. That fact encourages the emergence of schools labeled with religion with "extra" religious curriculum offers. So, the considerations in choosing a school from a Muslim family, in particular, can indirectly be seen from the curriculum character offered by the school and the character of its graduates. The purpose of this study was to determine the factors that influence parents in choosing an Islamic school. The method used is quantitative with 100 parents who have school-age children from grade 1 to grade 3 who have a middle to the upper economic background in the Bandung. The results of the study found that the factors of parents choosing an Islamic primary school that has primary school graduates accustomed to speaking good words such as please, sorry, thank you and Toyyibah sentences, accustomed to pray 5 times a day, reading the Quran, memorizing the Quran and language skills (Indonesian and English)